2016
DOI: 10.1037/hea0000384
|View full text |Cite
|
Sign up to set email alerts
|

Using fuzzy-trace theory to understand and improve health judgments, decisions, and behaviors: A literature review.

Abstract: Objective Fuzzy-trace theory is a dual-process model of memory, reasoning, judgment, and decision making that contrasts with traditional expectancy-value approaches. We review the literature applying fuzzy-trace theory to health with three aims: evaluating whether the theory’s basic distinctions have been validated empirically in the domain of health; determining whether these distinctions are useful in assessing, explaining, and predicting health-related psychological processes; and determining whether the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 59 publications
(129 reference statements)
4
106
1
1
Order By: Relevance
“…In addition, more research is needed regarding how one knows what the “right” gist should be, and how these representations are derived. There are established procedures that consistently yield predictive gist representations from a wide variety of respondents; these techniques include mathematical modeling (e.g., see Blalock & Reyna, 2016; Reyna & Brainerd, 2011). Deriving the right gist has also involved consulting experts and evidence-based clinical guidelines to summarize the essential bottom line—the gist—of decision-relevant information (e.g., Reyna & Lloyd, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, more research is needed regarding how one knows what the “right” gist should be, and how these representations are derived. There are established procedures that consistently yield predictive gist representations from a wide variety of respondents; these techniques include mathematical modeling (e.g., see Blalock & Reyna, 2016; Reyna & Brainerd, 2011). Deriving the right gist has also involved consulting experts and evidence-based clinical guidelines to summarize the essential bottom line—the gist—of decision-relevant information (e.g., Reyna & Lloyd, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically speaking, these qualitative gists were designed to incorporate the essence or bottom line of the medication’s risks and benefits, as opposed to precisely trading off magnitudes of risks and benefits. The endpoints were modeled on all-or-none categorical gist representations, the simplest level of gist, found to govern decision making in multiple contexts (e.g., Reyna & Mills, 2014; Wolfe et al, 2015; for a review, see Blalock & Reyna, 2016). The options ranged from seeing the risk as essentially nil to seeing the risk as all-encompassing (Stone, Yates, & Parker, 1994).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…[32][33][34][35] Research suggests that judgment and decision making is influenced most by those memory representations that are activated by characteristics of the decision-making context (e.g., environmental cues). 21 Thus, it seems likely that the impact of medication risk communications depends on a combination of (1) the information explicitly provided and (2) individuals' preexisting mental representations, rather than either of these factors in isolation.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…18,19 Overestimates of risk likelihood can make patients less willing to take a medication. 16,20 In a previous study by this research team that was guided by fuzzy trace theory (FTT), [21][22][23] it was demonstrated that simply informing individuals that a specific adverse effect may occur M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…People generally prefer to reason with the least precise gist representation that allows them to accomplish a cognitive task, such as making a choice (Reyna, Chick, Corbin, & Hsia, 2014). Moreover, experts in a given knowledge domain tend to rely more heavily on gist than novices (Blalock & Reyna, 2016;Reyna & Lloyd, 2006), and adults rely on gist representations more commonly than children (Brainerd, Reyna, & Ceci, 2008).…”
mentioning
confidence: 99%